A voz de Noeli em um podcast: uma análise dialógica da violência contra a mulher - Serafini, Marcos de Assis (2026)
This study aims primarily to understand the discursive tensions produced by the voices emerging from lexical selection, the hierarchy of information, and the description of the aggressor in the discourse of a woman who is a victim of domestic violence in a podcast. It is a qualitative study, of a basic and explanatory nature, with bibliographic and documentary procedures, based on Prodanov and Freitas (2013), and grounded in Bakhtinian theory, through the dialogical analysis of a podcast episode on violence against women. The corpus consists of the episode Noeli, from the podcast Amar por Elas, produced by the Associação Maria Rosa and publicly available on the YouTube platform, with a duration of 11 minutes and 40 seconds, published in 2023. The study presents a historical overview of laws aimed at combating violence against women in Brazil, highlighting legislative milestones that reflect the evolution of recognizing this issue as a social and human rights concern. Contributions from Saffioti (2015) are mobilized to unveil patriarchy as a structure of domination that permeates practices, institutions, and language. The research adopts a linguistic-discursive approach inspired by the theories of Bakhtin and the Circle (2010; 2015), with particular attention to dialogical relations. The analysis is especially supported by the systematization proposed by Beth Brait (2016), who, from the dialogical perspective of Bakhtin and the Circle, organizes the concrete utterance into four constitutive elements: (a) axiological load; (b) authorship; (c) addressee; and (d) dialogical relations. These principles guide the analytical path of Noeli’s discourse, understanding the text as a space of discursive tension. The dialogical interaction in Noeli’s account reflects her subjectivity, the voice of the aggressor, and the social influences on the victim’s discourse, offering a reading of how domestic violence is re-signified within a contemporary genre such as the podcast. Finally, the analysis demonstrates that, in the context of the podcast, the account refracts the experience of violence and makes explicit discursive tensions that reveal the presence of patriarchy as a historical structure that permeates and organizes the meanings produced.